2003
DOI: 10.1210/jc.2002-020645
|View full text |Cite
|
Sign up to set email alerts
|

Balance in Ghrelin and Leptin Plasma Levels in Anorexia Nervosa Patients and Constitutionally Thin Women

Abstract: Ghrelin, a 28-amino acid octanoylated peptide, has recently been identified in rat stomach as an endogenous ligand for the GH secretagogue receptor. In addition to GH-releasing properties, exogenous ghrelin injections exert orexigenic effects in both rodents and humans. As the endogenous peptide appears directly related to feeding behavior, we assessed its plasma levels in anorexia nervosa (AN) patients before and after renutrition and in constitutionally thin subjects with body mass indexes (BMIs) equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
205
4
16

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 311 publications
(248 citation statements)
references
References 54 publications
23
205
4
16
Order By: Relevance
“…Ghrelin, as is very well known, has profound orexigenic and adipogenic properties functioning as a signal for the hypothalamus when an increase in metabolic substrates is needed [15][16][17][18]28]. Therefore, it seems to be logic that ghrelin levels might be elevated in our patients, especially in the CDG group as an adaptive mechanism to lowered body weight, as seen in patients with anorexia nervosa and in obese subjects who lose weight with diet [29,30]. This suggestion cannot solely explain the elevated ghrelin levels in our patients because of two reasons; first, although our FSS group had lower body weight compared to controls, the difference did not reach statistical significance so that there should be another reason for the elevated ghrelin levels in our FSS group; second, in the multiple regression model, body weight was not the only predictor of serum ghrelin levels, with height SDS being the other independent determinant.…”
Section: Discussionmentioning
confidence: 97%
“…Ghrelin, as is very well known, has profound orexigenic and adipogenic properties functioning as a signal for the hypothalamus when an increase in metabolic substrates is needed [15][16][17][18]28]. Therefore, it seems to be logic that ghrelin levels might be elevated in our patients, especially in the CDG group as an adaptive mechanism to lowered body weight, as seen in patients with anorexia nervosa and in obese subjects who lose weight with diet [29,30]. This suggestion cannot solely explain the elevated ghrelin levels in our patients because of two reasons; first, although our FSS group had lower body weight compared to controls, the difference did not reach statistical significance so that there should be another reason for the elevated ghrelin levels in our FSS group; second, in the multiple regression model, body weight was not the only predictor of serum ghrelin levels, with height SDS being the other independent determinant.…”
Section: Discussionmentioning
confidence: 97%
“…Plasma ghrelin levels are highly elevated in patients with AN and return to normal after weight gain (Otto et al, 2001;Tolle et al, 2003). It has been shown that the bingeeating/purging subtype group had higher levels than the restricting subtype and still had higher levels than the controls after weight gain (Tanaka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Chez l'homme, en l'absence d'indice temporel ou de nourriture, l'augmentation de ghréline est bien corrélée à la sensation de faim, ce qui renforce l'hypothèse du rôle orexigène du peptide [40]. Il existe une corrélation négative entre l'indice de masse corporelle et les concentrations plasmatiques de ghréline à jeun : l'amaigrissement chez le sujet obèse s'accompagne d'une augmentation des niveaux de ghréline [41], tandis que l'inverse est observé avec la prise de poids en cas d'anorexie nerveuse [42]. Les patients insulinorésistants ou souffrant d'un diabète de type 2 présentent également de faibles concentrations de ghréline cir- Effets paracrines sur la prolifération Testostérone concentrations de ghréline sont abaissées dans tous les cas d'obésité humaine d'origine génétique (déficience en leptine, mutations du récepteur de la leptine ou du récepteur 4 de la mélanocortine, MC4), ou hypothalamique (craniopharyngiomes), elles sont particulièrement élevées dans le syndrome de Prader-Willi [46], du même ordre de grandeur qu'au cours de l'anorexie nerveuse : il a été proposé que ces concentrations très élevées de ghréline pouvaient contribuer à l'hyperphagie sévère des enfants atteints.…”
Section: Et La Clinique Dans Tout çà ?unclassified